Accuracy of left atrial fibrosis detection with cardiac magnetic resonance: correlation of late gadolinium enhancement with endocardial voltage and conduction velocity. Issue 3 (23rd November 2020) - Caixal, Gala; Alarcón, Francisco; Althoff, Till F; Nuñez-Garcia, Marta; Benito, Eva Maria; Borràs, Roger; Perea, Rosario Jesus; Prat-González, Susana; Garre, Paz; Soto-Iglesias, David; Gunturitz, Clara; Cozzari, Jennifer; et al.
Abstract: Aims: Myocardial fibrosis is a hallmark of atrial fibrillation (AF) and its characterization could be used to guide ablation procedures. Late gadolinium enhanced-magnetic resonance imaging (LGE-MRI) detects areas of atrial fibrosis. However, its accuracy remains controversial. We aimed to analyse the accuracy of LGE-MRI to identify left atrial (LA) arrhythmogenic substrate by analysing voltage and conduction velocity at the areas of LGE. Methods and results: Late gadolinium enhanced-magnetic resonance imaging was performed before ablation in 16 patients. Atrial wall intensity was normalized to blood pool and classified as healthy, interstitial fibrosis, and dense scar tissue depending of the resulting image intensity ratio. Bipolar voltage and local conduction velocity were measured in LA with high-density electroanatomic maps recorded in sinus rhythm and subsequently projected into the LGE-MRI. A semi-automatic, point-by-point correlation was made between LGE-MRI and electroanatomical mapping. Mean bipolar voltage and local velocity progressively decreased from healthy to interstitial fibrosis to scar. There was a significant negative correlation between LGE with voltage ( r = −0.39, P < 0.001) and conduction velocity ( r = −0.25, P < 0.001). In patients showing dilated atria (LA diameter ≥45 mm) the conduction velocity predictive capacity of LGE-MRI was weaker ( r = −0.40 ± 0.09 vs. –0.20 ± 0.13, P = 0.02). Conclusions: Areas with higher LGE show lower voltage and slower conduction in sinus rhythm. The enhancement intensity correlates with bipolar voltage and conduction velocity in a point-by-point analysis. The performance of LGE-MRI in assessing local velocity might be reduced in patients with dilated atria (LA diameter ≥45).